The influence of social commerce on consumer decision making: a case study of perishable pastry products - A. Rahman, Faradewi Bee; Hanafiah, Mohd Hafiz; Mohd Zahari, Mohd Salehuddin; Benedict Jipiu, Lovelyna (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
This study examines the relationship between social commerce adoption determinants, perceived trust, and purchase behavior among pastry product consumers. Data from 409 consumers were collected via an online survey and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The findings reveal that consumers perceive social commerce as effortless, engaging, enjoyable, trustworthy, simple to use, and time- saving, motivating them to purchase pastry products through social commerce platforms. The study offers insights for social commerce researchers and marketers, particularly regarding perishable products. It contributes to the understanding of technology acceptance theory by elucidating the determinants of social commerce adoption among consumers in the pastry products domain.